The Behavioural Transmission Mechanism of Meme Stocks – Evidence from Sentiment, Herding and Volatility (2018–2023) - Pochylý, Jakub (2025)
Meme stocks follow sentiment, not fundamentals. Their movements are shaped by belief, imitation, and collective mood. This thesis examines the behavioural transmission mechanism behind their dynamics—how sentiment leads to herding, volatility, and ultimately return formation. Mood is extracted from Reddit (WallStreetBets) using NLP models and tested on selected stocks between 2018 and 2023. The findings show that sentiment acts not only as a trigger but as structure—shaping coordination and amplifying risk asymmetrically. Positive sentiment tends to fragment investor behaviour, while negative sentiment fosters defensive convergence. Meme stocks are best understood as expressions of collective psychology in a market environment influenced by emotion.